(untitled) (Eurasian Journal of Humanities and Social Sciences, 2026)
The rapid development of artificial intelligence (AI) has significantly influenced the field of education, including pedagogical sciences. This article explores how artificial intelligence is being applied in pedagogical research and educational practice, with particular attention to its role in supporting personalized learning, improving assessment procedures, and enhancing overall teaching effectiveness. The study adopts a qualitative analytical approach, examining key theoretical perspectives, existing practices of AI use in educational settings, and challenges related to its integration. The findings indicate that artificial intelligence can support pedagogical innovation and evidence-based decision-making when applied responsibly. However, effective implementation requires teachers’ pedagogical competence, digital literacy, and careful consideration of ethical and methodological issues.